IMMUNE RESPONSE TO COVID-19 COMPARED TO THE IMMUNE RESPONSE TO SARS, MERS AND INFLUENZA - Velo Markovski (Problems of Infectious and Parasitic Diseases, 2020)
The course, form and outcome of an acute respiratory illness, as well as its patho-histological features largely depend on the level of inflammatory cytokines. The most important proinflammatory cytokines and chemokines are: IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-17A, IFN-γ, TNF-α and GM-CSF. There are many similarities in the human immune response to influenza, SARS and MERS-CoV. Available studies of COVID-19 show a completely different immune response, i.e. immunological indifference or suppression.